Endurance of Renewable Polymer Composite to UV Irradiation - Normunira Mat Hassan, Nik; Zafiah Mohd Rus, Anika; Mohamed Yusop, Fatimah; Marsi, Noraini; Sulong, Nurulsaidatulsyida; Abu Bakar, Bachik; Abd Rashid, Razlin; Afzanizam Samiran, Nor (International Journal of Engineering and Technology, 2019)
Polymer degradation occurs under the influence of sunlight and almost all polymer require stabilization to resist the adverse effect. The polymer degradation leads to discoloration when exposed to ultraviolet (UV) irradiation. In this study the renewable polymer composite was produce by preparation of renewable monomer from waste vegetable oil, crosslink with polymethane polyphenyl isocyanate, distilled water and titanium dioxide (TiO2) as filler. The fabrication method of renewable polymer composite in which to produce RF and its composites (RFC) by manual casting method while for CR and CRC using hot compression moulding technique. The density, porosity and morphology structure of RF, RFC, CR and CRC were measured endurance to UV irradiation exposure for a period of 1000 hours by UV Whetherometer apparatus. The density of RF and RFC exhibit no significant changes after UV irradiation exposure while porosity shows decrease with increasing of percentage of TiO2 filler loading. The morphology structure measurement gives no significant changes of pore cell size of renewable polymer with the increased of filler loading and UV irradiation exposure by different fabrication technique. From observation, discoloration of RF and RFC is less dark as compared to CR and CRC. This is due to the different fabrication technique gives some effects for surface of renewable polymer due to application of heat during hot compression technique. The discoloration surface structure of RF, RFC, CR and CRC were changed from yellow to dark yellow colour after UV irradiation exposure. This is due to formation of quinone structure product produced from the photolysis of renewable polymer under UV irradiation exposure. Hence, TiO2 is used for UV absorber to delay discoloration on the surface of renewable polymer.Â